From virus isolation to metagenome generation for investigating viral diversity in deep-sea sediments - Cinzia Corinaldesi (Nature Portfolio, 2017)
Abstract Viruses are the most abundant and, likely, one of the most diverse biological components in the oceans. By infecting their hosts, they play key roles in biogeochemical cycles and ecosystem functioning at a global scale. The ocean interior hosts most of the microbial life, and, despite deep-sea sediments represent the main repository of this component and the largest biome on Earth, viral diversity in these ecosystems remains almost completely unknown. We compared a physical-chemical procedure and a previously published sediment washing-based procedure for isolating viruses from benthic deep-sea ecosystems to generate viromes through high-throughput sequencing. The procedure based on a physical-chemical dislodgment of viral particles from the sediments, followed by vacuum filtration was much more efficient allowing us to recover >85% of the extractable viruses. By using this procedure, a high fraction of viral DNA was recovered and new viromes from different benthic deep-sea sites were generated. Such viromes were diversified in terms of both viral families and putative functions. Overall, the results presented here provide new insights for evaluating benthic deep-sea viral diversity through metagenomic analyses, and reveal that deep-sea sediments are a hot spot of novel viral genotypes and functions.